2010
DOI: 10.4028/www.scientific.net/msf.636-637.1434
|View full text |Cite
|
Sign up to set email alerts
|

Printed Circuit Boards Recycling: Characterization of Granulometric Fractions from Shredding Process

Abstract: In electronic appliances, printed circuit boards (PCB) represent an important component, containing high grade of valuable metals, besides organic resins and some ceramic materials. Copper is the major metal in PBC’s composition (normally higher than 20% w/w) but many other secondary and minor metal elements, including precious metals, are found in PCB’s. Recycling of PCB´s involves firstly the shredding operation, which is crucial in order to liberate particles from different materials, allowing its further p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“… (a) Feldman (1993) [ 13 ]; (b) Menetti et al (1995) [ 14 ]; (c) Iji et al (1997) [ 15 ]; (d) Veit et al (2002) [ 16 ]; (e) Zhao et al (2004) [ 17 ]; (f) Kim et al (2004) [ 18 ]; (g) Wang et al (2005) [ 19 ]; (h) Creamer et al (2006) [ 20 ]; (i) Marco et al (2008) [ 21 ]; (j) Hino et al (2009) [ 2 ]; (k) Das et al (2009) [ 22 ]; (l) Yoo et al (2009) [ 23 ]; (m) Oliveira et al (2010) [ 4 ]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… (a) Feldman (1993) [ 13 ]; (b) Menetti et al (1995) [ 14 ]; (c) Iji et al (1997) [ 15 ]; (d) Veit et al (2002) [ 16 ]; (e) Zhao et al (2004) [ 17 ]; (f) Kim et al (2004) [ 18 ]; (g) Wang et al (2005) [ 19 ]; (h) Creamer et al (2006) [ 20 ]; (i) Marco et al (2008) [ 21 ]; (j) Hino et al (2009) [ 2 ]; (k) Das et al (2009) [ 22 ]; (l) Yoo et al (2009) [ 23 ]; (m) Oliveira et al (2010) [ 4 ]. …”
Section: Resultsmentioning
confidence: 99%
“…In Europe, 7 million tons of electronic waste is generated annually, and this figure is estimated to be increasing at 3%–5% a year [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chapter 9: Column bioleaching to recover copper from e-waste found that the higher the particle size, the lower the copper concentration, but they performed the experiments until 3 mm. Therefore, the results found in this work are in accordance to Oliveira et al (2010) in this range size but this work demonstrated that this affirmation was not correct when higher particle size are analysed. For this reason, it is important to analyse the copper content of the particle size used in each experiments for non-erroneous conclusions.…”
Section: Metalscontrasting
confidence: 48%
“…Chapter 9: Column bioleaching to recover copper from e-waste Despite the heterogeneity of the PCBs mentioned above, Oliveira et al (2010) demonstrated that the metal distribution also depends on the particle size fraction. In particular, they concluded that the major elements such as copper, tin and lead had higher concentrations in the particle size range of 0.3 and 1.5 mm and they substantially decrease in lower fractions.…”
Section: Bioleaching Experimentsmentioning
confidence: 99%
“…However, Pd was very concentrated in the [1.4-1.0] mm class with up to 70 % for this metal. Oliveira et al (2010) showed that gold (Au) distribution in granulometric fractions of ground PCBs did not depend on the size portions while silver (Ag) concentration increased when the size of particle portions decreased.…”
Section: Distribution Of Metals In the Granulometric Fractions Of Cru...mentioning
confidence: 99%